Consumption-led expansions are toxic for future output growth - Matti E. E. Virén (Aboa Centre for Economics (ACE), 2022)
When assessing future growth prospects, does it matter how the economy grows now? In other words, does the current structure of demand affect future growth? This question is analyzed in our paper by using global and EU panel data. The result is quite striking: consumption-led growth - either in terms of private or public or total consumption - leads to slower growth compared with investment-led or exports-led growth. The same qualitative result emerges irrespectively of the length of the past growth period (lag window). It is only that the more often the past is characterized by consumption-led growth the slower the growth rate in the future. This is surely important news from the point of view of both structural and cyclical policies.
Keywords: E21; E32; E50; F43; O40; 330; Economic growth; demand management; consumption-ledgrowth